1990
DOI: 10.1258/002367790780866182
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and sex on seven elements in Sprague-Dawley rat organs

Abstract: SummaryThis study reports age-related changes in 7 element (iron, copper, zinc, manganese, mercury, cadmium and lead) concentrations in the liver, kidney and brain of male and female Sprague-Dawley rats from 1 to 364 days of age. Atomic absorption spectrometry was used for the measurements.Copper, mercury and cadmium in the male and female kidneys increased from weaning until 127 days of age, as did iron concentrations in the female liver and kidney. After 127 days, especially, the copper concentration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…However, nontreated female mice had significantly higher liver iron concentration than aged matched males. Age and sex differences in tissue iron concentrations were also described in rats (Uchino et al 1990).…”
Section: Discussionmentioning
confidence: 93%
“…However, nontreated female mice had significantly higher liver iron concentration than aged matched males. Age and sex differences in tissue iron concentrations were also described in rats (Uchino et al 1990).…”
Section: Discussionmentioning
confidence: 93%
“…There is considerable evidence that copper metabolism differs between male and female animals. Concentrations of liver copper and liver superoxide dismutase differ between female and male animals and plasma copper and ceruloplasmin have been reported higher in women in a study comparing them with men [7,23]. Women on hormonal contraception or pregnant women tend to have higher levels of Cu and ceruloplasmin in plasma in comparison to nonpregnant, not on hormonal contraception women [7].…”
Section: Discussionmentioning
confidence: 98%
“…We used female rats because their body weights become stable in adulthood (starting at about 3 months) [19]. Studies by Cantillon and Bradford [20] showed that there is no difference between the male and female rat in the contractile properties of upper airway muscles, both in young and old animals.…”
Section: Methodsmentioning
confidence: 99%